Tityus serrulatus Scorpion Venom-Induced Nociceptive Responses Depend on TRPV1, Immune Cells, and Pro-Inflammatory Cytokines - Camila R. Ferraz; Marília F. Manchope; Mariana M. Bertozzi; Telma Saraiva-Santos; Ketlem C. Andrade; Anelise Franciosi; Tiago H. Zaninelli; Julia Bagatim-Souza; Sergio M. Borghi; Denise M. Cândido; Thiago M. Cunha; Rubia Casagrande; et al. (Toxins)
For centuries, researchers have been fascinated by the composition of scorpion venom and its local and systemic effects on humans. During a sting, scorpions inject peptides and proteins that can affect immune cells and neurons. While the immune and nervous systems have been studied independently in the context of scorpion stings, here we reveal part of the mechanism by which Tityus serrulatus venom induces hyperalgesia in mice. Through behavioral, immune, imaging assays, and mice genetics, we demonstrate evidence of neuroimmune crosstalk during scorpion stings. Tityus serrulatus venom induced mechanical and thermal hyperalgesia in a dose-dependent manner, as well as overt pain-like behavior. The venom directly activated dorsal root ganglia neurons and increased the recruitment of macrophages and neutrophils, releasing pro-inflammatory cytokines TNF-α and IL-1β. Blocking TRPV1+ neurons, TNF-α, IL-1β, and NFκB reduced the mechanical and thermal hyperalgesia, overt pain-like behavior, and the migration of macrophages and neutrophils induced by Tityus serrulatus venom. Collectively, Tityus serrulatus venom targets primary afferent nociceptive TRPV1+ neurons to induce hyperalgesia through the recruitment of macrophages and neutrophils and the release of pro-inflammatory cytokines.